Increasing Teacher’s Professional Commitment Through Strengthening of Servant Leadership, Personality, Work Motivation, and Trust on Elementary School Teacher - Nurlaila, Hanik; Setyaningsih, Sri; Sunardi, Oding (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
This research aimed to analyze the influence of servant leadership, personality, work motivation and trust on the professional commitment of elementary school teachers. The research, conducted in 157 accredited "A" public elementary schools in Depok City, involved 1,170 teachers. The one-year study utilized survey methods and a quantitative approach, focusing on causal relationships among variables. Variables studied included professional commitment (Y), servant leadership (X1), personality (X2), work motivation (X3), and trust (X4). Path analysis separated direct and indirect effects of independent variables on the dependent variable, seeking optimal strategies to enhance teachers' professional commitment. Results indicate that strengthening servant leadership, personality, work motivation, and trust directly enhances professional commitment, with indirect influence through trust and work motivation. Recommendations include improving indicators in weak variables, emphasizing sincerity in tasks, love for the job, and feedback. Optimal strategies involve improvements in servant leadership, trust, and work motivation to enhance professional commitment, providing clear guidance for implementation in the context of the research.